Pola Pembinaan Akhlak Pada Siswa Kelas VII di Madrasah Tsanawiyah Satu Atap Minhajul Abidin Janti Jogoroto Jombang - Moh. Irfan; Khoirul Huda (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
This study aims to answer the main issues regarding the Implementation of Student Moral Development at MTs Satu Atap Minhajul Abidin Janti Jogoroto Jombang. This type of research is descriptive qualitative. The data collection uses interview, observation, and documentation methods. The primary data sources are school principals, moral aqeedah teachers and MTs Satu Atap Minhajul Abidin Janti Jogoroto Jombang students, while the secondary data are books related to children's moral development. The data analysis technique uses data reduction analysis techniques (data reduction), data display (data presentation), and verification (drawing conclusions). The results of the study can be concluded that the pattern of student moral development at Mts. Satu Atap Minhajul Abidin Janti Jogoroto Jombang uses several methods such as through example, habituation, advice or understanding, and giving punishment or warning. However, in research, the authors found that the process of fostering student morals at MTs Satu Atap Minhajul Abidin Janti Jogoroto Jombang arises from the personal characteristics of students who lack parental attention to their children, so that students still practice deviant behavior or have bad morals.